Beef Floss Efficiency in Women Farmer Group Karya Sejahtera in Wawasan Village Tanjungsari Districts - Sri Handayani; Chandra Utami Wirawati; S. Sarono; Eko Win Kenali; Annisa Fitri (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2021)
As the Ongole Cross-Breed breeding cluster, cattle farms in the Wawasan village area had applied beef products of diversification beef floss to solve fluctuations in cattle prices, low farm income, and seasonal cattle sales. This study purposed to analyze the economic efficiency of beef floss production in KWT Karya Sejahtera. The basic method of this research was descriptive-analytic. The research location was chosen purposively by KWT Karya Sejahtera as the production center for beef floss in Tanjungsari District. The analytical method was cost analysis, profitability, and business efficiency. The analysis results and discussion showed that the beef floss production was efficiently managed. It was indicated by the efficiency value of the beef floss business of 1.3 (more than 1). As a whole, beef floss production contributes an additional 20% of what is run by farmers, so this business is feasible to run economically.